A New Sensitive Sensor Test for Capturing and Evaluating Bacteria and Viruses in Airborne AerosolsViruses in Airborne Aerosols - Pernica, Roman; Szabó, Zoltán; Čáp, Martin; Pavliš, Oto; Kubíčková, Pavla; Zukal, Jiří; Fiala, Pavel (MDPI, 2025)
In this paper, the authors describe an electromagnetic–hydrodynamic (EMHD) model of the airborne microbiological agent detection concept for the design of a sensor to identify the presence of airborne bacteria and viruses. Based on the model and a laboratory test, a methodology was proposed for the capture and subsequent detection of low-concentration bacterial and viral agents in airborne aerosols. A physical–biological approach was proposed to detect microorganisms based on their physical properties. The principle was validated in the laboratory on samples of defined concentrated water aerosols of Bacillus subtilis (BS) and feline infectious peritonitis virus (FIVP). Repeated tests with different concentrations were performed in the laboratory conditions.

In this paper, the authors describe an electromagnetic–hydrodynamic (EMHD) model of the airborne microbiological agent detection concept for the design of a sensor to identify the presence of airborne bacteria and viruses. Based on the model and a laboratory test, a methodology was proposed for the capture and subsequent detection of low-concentration bacterial and viral agents in airborne aerosols. A physical–biological approach was proposed to detect microorganisms based on their physical properties. The principle was validated in the laboratory on samples of defined concentrated water aerosols of Bacillus subtilis (BS) and feline infectious peritonitis virus (FIVP). Repeated tests with different concentrations were performed in the laboratory conditions.
A New Sensitive Sensor Test for Capturing and Evaluating Bacteria and Viruses in Airborne AerosolsViruses in Airborne Aerosols
Keywords: sensor; PCR; aerosol; COVID-19; virus; bacteria; detection; electromagnetic field; sensor; PCR; aerosol; COVID-19; virus; bacteria; detection; electromagnetic field